Developing Interactive Powerpoint Media to Teach Reading for 8th Grade students at MTs Ma'arif NU Gandusari - Nikmah, Binti Hainun; Makrifah, Istina Atul; Saifudin, Ahmad (Universitas Nahdlatul Ulama Blitar, 2022)
This study aims to know the process and result in developing interactive PowerPoint media to teach reading. The problems of this study are that the teacher has difficulty identifying students' weaknesses, sometimes still lacks ideas, and does not have enough time to develop interactive learning media. Then students are quickly bored in learning. Therefore, the researcher concluded that interactive PowerPoint media could attract students' learning interest in reading. The researcher developed it and offered it as a learning medium at MTs Ma'arif NU Gandusari. The subjects were class VIIIa students consisting of 23 students. This study was research and development, and the method used the R&D method developed by Borg and Gall, and there are ten steps. However, due to the pandemic, limited time, and opportunities from school, it was only a one-time trial; the researcher simplified it to eight-step. Validation result: The validator media expert obtained 82.5%, and the material expert obtained a percentage of 90%. Assessment by student satisfaction response obtained a percentage of 93%. From the results of the media and material expert validation questionnaire and student response questionnaires, interactive PowerPoint media has a validity that is included in the very decent category for use.